Analisis Kepatuhan Syariah pada KSSPS BMT Guna Lestari - Henny Ishalia Pratiwi; Miswan Ansori (CV. Creative Tugu Pena, 2024)
This research aims to analyze the level of sharia compliance at KSPPS BMT Guna Lestari. The main focus of this research is to identify factors that influence sharia compliance and the role of the Sharia Supervisory Board (DPS) in maintaining operational integrity in accordance with sharia principles. The method used is a qualitative approach with case studies, where data is collected through semi-structured interviews, observation and documentation. The research results show that sharia compliance at KSPPS BMT Guna Lestari is influenced by the availability of DPS resources, reporting and coordination systems, as well as the culture of sharia compliance within the organization. DPS plays a significant role, although challenges such as limited resources and lack of employee technical understanding regarding sharia still exist. This research suggests the need for better resource allocation for DPS as well as more in-depth training for employees to improve sharia compliance.